Raman Micro-Spectroscopy of Dental Pulp Stem Cells: An Approach to Monitor the Effects of Cone Beam Computed Tomography Low-Dose Ionizing Radiation. (3rd May 2019) - Simon, Ioana; Hedesiu, Mihaela; Virag, Piroska; Salmon, Benjamin; Tarmure, Viorica; Baciut, Mihaela; Bran, Simion; Jacobs, Reinhilde; Falamas, Alexandra
Abstract: The objective of this study was to determine the molecular and biochemical changes in dental pulp stem cells (DPSCs) due to consecutive low-dose ionizing radiation exposures using label-free Raman micro-spectroscopy (RMS). Ionizing radiation produces biological damage leading to health effects of varying severity. The effects and subsequent health implications caused by exposure to low-dose radiation, such as diagnostic exposure, remain ambiguous. We identified Raman biomarkers characteristic to low-dose cone beam computed tomography (CBCT) irradiation of the DPSCs. The biomarkers were monitored inside the cells using the relative intensity distribution of the 785 and 1734 cm −1 bands. The control cells presented a higher relative intensity of the nucleic acid specific Raman bands, whereas the irradiated cells revealed an increased intensity of the lipid-induced bands. The results obtained in this study demonstrate the capability of RMS for the detection of cell response to diagnostic radiation dose levels. This may indicate the potential of the technique for future applications such as monitoring the radiation responses in pediatric patients suffering repeated radiological exposures.